EVALUASI NILAI BIOLOGIS BAHAN KERING DAN BAHAN ORGANIK PAKAN LENGKAP BERBASIS TEBON JAGUNG PADA SAPI PERAH - Manganang, Meylin; Tuturoong, Ronny A.V.; Pendong, Abraham F.; Waani, Merci R. (ZOOTEC, 2020)
EVALUATION OF BIOLOGICAL VALUE OF DRY MATTER AND ORGANIC MATTER COMPLETE FEED BASED ON CORN FORAGE IN DAIRY COWS. This aim of this study was to determine intakes and digestibility of the dry matter and organic matter of complete feed based on corn forage. 14 FH cows weighing 300-400 kg were used in this research. The feed treatments consist of  Ra (30% concentrate + 70% corn forage), and  Rb (30% concentrate + 35% corn forage +    35% king grass). This experiment arranged in a statistical method of t-test two sample assuming unequal variance. The variables observed were intakes and digestibilities of both dry matter and organic. The results shows that the intakes of both dry matter and organic matter in the Ra were not significantly different from the Rb (P> 0.05). The dry matter digestibility of Rb were highly significant different from Ra (P<0.01), as well as organic matter digestibility of Rb was also significantly different from Ra (P <0.05). It is concluded that complete feed consisting of concentrate, corn forage and king grass was obtained the best digestibilities of both dry matter and organic matter.